Clinical Presentation of Uterine Fibroids in Nnewi, Nigeria: A 5-year Review - Ezeama, CO (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Uterine leiomyomas are the commonest benign tumors in women, with a higher preponderance amongst Africans. Several etiological factors have been suggested, with subtle variations in clinical presentation being reported in different studies. This may constitute a determinant for the management measures undertaken. AIM: To review the clinical presentation and management measures undertaken for uterine leiomyoma. SUBJECTS AND METHODS: A retrospective study was conducted at Nnamdi Azikiwe University Teaching Hospital (NAUTH), Nnewi, from January 2002 to December 2006. A review of case records of patients with a diagnosis of uterine leiomyoma was done. The data were analyzed and presented in tables using comparative percentages. RESULTS: Uterine leiomyoma constituted 117 of the 1094 gynecological admissions during this study period (10.7%, 117/1094). The mean (SD) age of presentation was 35.7 (6.1) years. Most of the patients were nulliparous (76.7%, 79/103) and 51.5% (53/103) were married. The commonest mode of presentation was lower abdominal mass (66.9%, 67/103) and the least was recurrent abortion (1%, 1/103). Surgery was employed in all cases, with myomectomy being the commonest modality used in 90.3% (93/103) of cases. The common postoperative complications were prolonged pain (49.5%, 51/103) and postoperative pyrexia (34.9%, 36/103). CONCLUSION: The symptom of lower abdominal mass correlates with late presentations in our setting. This makes the application of newer therapies like laparoscopic myomectomy difficult even when they are available. Other therapies which are independent of fibroid size (like uterine artery embolization) are not readily available in our environment. This further emphasizes the importance of myomectomy as the most important treatment modality in our environment.